KEABSAHAN CRYPTOCURRENCY PADA SARANA INVESTASI DI INDONESIA - Ary Setiawan Prasetyo; Rosalinda Elsina Latumahina (Gapenas Publisher, 2023)
Cryptocurrency is an asset and as a digital currency that functions as a medium of exchange in digital transactions. Another function of Cryptocurrency apart from being a means of payment and currency is as an investment tool. In addition, cryptocurrencies can be used as a means of investment, this is due to the large demand for these assets. Cryptocurrencies that are growing so rapidly do not rule out the possibility of a crime, one of the crimes that occur in Cryptocurrency is taking investors' assets away by Cryptocurrency developers which causes investors to lose assets or commonly known as Rug Pull. For this reason, this study aims to analyze the legality of Cryptocurrency based on applicable regulations in Indonesia and also the legality of Cryptocurrency Exchanges in Indonesia. The type of research method used in this research is normative legal research by examining the laws and regulations in force in Indonesia, the opinions of scholars, and also legal theory by using a type of approach method through legislation and also a conceptual approach and by using collection techniques. legal materials through literature study using legal materials processing techniques by way of legal refinement to clarify the requirements of Cryptocurrency as a means of investment in Indonesia. After conducting the research, it can be concluded that to provide comfort to Cryptocurrency investors, an institution that functions as a supervisor is needed so that the purchased Crypto assets can be properly monitored and recorded so that investors can be legally protected